2018
DOI: 10.1021/acs.iecr.8b05291
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Dyes from Waste Solutions by Anodic Oxidation on an Array of Horizontal Graphite Rods Anodes

Abstract: In this work, degradation of two dyes, methylene blue and methyl blue, by anodic oxidation in a new arranged electrochemical cell is investigated in the presence of Cl − ions. The cell consists of an array of graphite rods working as the anode placed horizontally between two horizontal stainless steel screens cathodes. The cell performance is tested in terms of the color removal efficiency, COD removal, electrical energy consumption, anode efficiency, and current efficiency. Parameters studied are initial dye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 75 publications
0
12
0
1
Order By: Relevance
“…The sn values shown in Table 1 are one order of magnitude lower in comparison with 1.76 m 3 m -3 h -1 obtained for the 88% of MB decolouration by using an initial MB concentration of 100 mg dm -3 at 42.55 mA cm -2 in a cell with graphite as anode and stainless steel as cathode [71]. This may be due to the large volume of the electrolyte (300 cm 3 ) in comparison to the small electrode area (1 cm 2 ) employed.…”
Section: Time / Minmentioning
confidence: 74%
“…The sn values shown in Table 1 are one order of magnitude lower in comparison with 1.76 m 3 m -3 h -1 obtained for the 88% of MB decolouration by using an initial MB concentration of 100 mg dm -3 at 42.55 mA cm -2 in a cell with graphite as anode and stainless steel as cathode [71]. This may be due to the large volume of the electrolyte (300 cm 3 ) in comparison to the small electrode area (1 cm 2 ) employed.…”
Section: Time / Minmentioning
confidence: 74%
“…However, only 53% of the Cr(VI) removed at the lowest rpm and on using 2 g of iron powder. This trend is attributed to an increase in the diffusion rate of Cr(VI) solution, as rpm increases, which decreases the diff usion layer thickness on iron powder and increases iron reactivity [Abdel-Aziz et al, 2018].…”
Section: Eff Ect Of Rotation Speedmentioning
confidence: 97%
“…Maximum color removal efficiency was obtained after 70 minutes of electrolysis at 79 mA.cm −2 current density. Abdel-Aziz et al [32] reported the anodic oxidation of methylene blue (50 ppm) azo dye on graphite anode in aqueous (2.5 g.L −1 NaCl) solution at pH 3.0. A maximum color removal of 94% was achieved after 30 min treatment time at 42.55 mA.cm −2 current density.…”
Section: Graphitementioning
confidence: 99%